1990
DOI: 10.1111/j.1600-0749.1990.tb00255.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐selective Action of 4‐Hydroxyanisole on Melanoma Cells In Vivo

Abstract: In order to clarify the role of tyrosinase (E.C. 1.14.18.1) in the cytotoxicity of 4-hydroxyanisole (4HA) in vivo, we have compared the therapeutic effects of 4HA on the B16 melanoma and Harding-Passey melanoma, which differ significantly in their tyrosinase content. The observed therapeutic effects are moderate and similar in both tumors. Therefore, there is no evidence for an increase of the cytotoxic effect of 4HA by tyrosinase in vivo. Application of 4HA to mice carrying B16 melanoma and Harding-Passey mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1991
1991
1997
1997

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The toxicity for these compounds was the same in the normal non-tumorigenic parental cell line and the two tumorigenic transformed lines R19 and CIRAS I. These data agree with earlier published results that 4HA has nonspecific toxicity effects (Schwiabe et al, 1990;Wallevik et al, 1984). In addition, we have shown that transfection by J L ' O 0 2 6 6 8 10 12…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The toxicity for these compounds was the same in the normal non-tumorigenic parental cell line and the two tumorigenic transformed lines R19 and CIRAS I. These data agree with earlier published results that 4HA has nonspecific toxicity effects (Schwiabe et al, 1990;Wallevik et al, 1984). In addition, we have shown that transfection by J L ' O 0 2 6 6 8 10 12…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies have shown that 4-hydroxyanisole (4HA) and other phenolic compounds are known to have cytotoxic activity against pigmented cells such as melanocytes, as well as pigmented melanoma (Kanclerz and Chapman, 1986;Kanclerz and Zbytniewski, 1981;Meyskens, 1984;Riley, 1984;Riley et al, 1975). However, further studies did not all agree and some showed specific activity of 4HA against pigmented cells (Bleehen, 1976;Dewey et al, 1977;Kulkarne and Nathanson, 1989;Meyskens, 1984), while others showed non-specific activity against a wide range of different cells (Schwiabe et al, 1990;Thody et al, 1988;Wallevik et al, 1984). In fact, one study indicated activity toward non-pigmented cells but increased activity against pigmented cells, and it was proposed that there were possibly two mechanisms of action, a specifically directed mechanism through tyrosinase conversion of 4HA into toxic radicals and a non-specific mode of action of 4HA on the inhibition of DNA and RNA synthesis (Kulkarne and Nathanson, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…This is made evident from the study of 4HA. Many studies on this substrate, which is used in melanoma therapy, have been published (10)(11)(12)(13). However, the behavior of 4HA as tyrosinase substrate has never been properly detailed.…”
Section: Introductionmentioning
confidence: 99%
“…Riley and his associates [21] indicated that 4-hydroxyanisole is a potent depigmenting agent and has some in vivo and in vitro antimelanoma effect in animals and humans. A number of recent studies, however, indicated that 4-hydroxyanisole does not have any selective cytotoxicity to pigment cells [22].…”
Section: Phenolsmentioning
confidence: 98%